The Hajj legacy and Saudi Arabia’s exemplary response to COVID-19 - Alsaleh, Ghadah; Balkhi, Bander; Alahmari, Ahmed; Khan, Anas (Frontiers in Public Health, 2025)
The COVID-19 pandemic required strong public health measures globally. Saudi Arabia’s effective pandemic management, leveraging its experience with mass gatherings such as the Hajj pilgrimage, has been lauded globally. This study was developed using a narrative synthesis approach, based on a structured review of peer-reviewed literature (PubMed and Scopus) and official sources (Saudi MoH and the WHO) covering March 2020–December 2024. This study examines Saudi Arabia’s response to the COVID-19 pandemic, with particular emphasis on the strategies implemented to safeguard the Hajj pilgrimage. The analysis is framed within the context of the World Health Organization’s (WHO) COVID-19 After Action Review pillars, providing a structured evaluation of the Kingdom’s efforts to mitigate risks and protect both pilgrims and the broader population. Topics covered include country-level coordination, risk communication, surveillance, border health, national laboratory systems, infection prevention, case management, operational support, and essential health services. Findings show that preexisting infrastructure and mass-gathering expertise enabled rapid activation of multisectoral task forces, adaptive risk-communication campaigns, and scalable testing and isolation protocols. The Hajj legacy strengthened laboratory diagnostics and surge staffing, informed border screening algorithms, and guided large-event risk assessments. Integrating mass-gathering experience with WHO’s framework fostered resilience to complex health emergencies. Saudi Arabia’s model offers actionable insights for other nations seeking to harness cultural and organizational strengths in pandemic preparedness.